Surgery of the nasal septum and turbinates - Matthias, Christoph (German Medical Science GMS Publishing House, 2008)
The following article presents nasal septum and turbinate surgery. First an overview with special consideration of the anatomical and physiological background is given followed by indications for surgical procedures. Key steps of the gold standard procedure first described by Cottle and common variations are presented. Furthermore, some techniques dealing with special problems of the septumplasty are discussed followed by an overview on complications and long term results. However, it should be mentioned that studies on surgical procedures of the nasal septum are still not sufficient as higher evidence levels are very rare. Within a separated chapter techniques for closure of septum perforations are presented and indications particularly in the background of the standard procedure of bridge flaps forwarded by Schultz-Coulon are discussed. The second part focusses on turbinate surgery. Accordingly, anatomical and physiological basics are presented followed by indications for surgical procedures and the surgical steps of different procedures as well as postsurgical treatment and long term results.